The University Policlinic pedagogic pattern: expression of the new formative paradigm. - Maricel Castellanos González; Irma Pasarón Pérez; Jorge Cañellas Granda; Asbely Yera Sánchez; Zenia Sánchez García (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2007)
Since the creation of the National Health System a steady, progressive, and gradual process of paradigm change has taken place in our country in medical sciences, under materialistic philosophy conceptions until arriving in our days to the new pedagogic model for basic integral general doctor's formation, sustained by the working education strength as fundamental principle. It implies to locate the student under professionals conditions to solve real or potential problems, using the teacher's behaviour, and accompanying these solutions with studies in the own performance process. In this sense, it acquires great importance the current teaching aids revolution, since it facilitates the most up-to-date knowledge, being this new model the expression of the formative socio -doctor paradigm.